PERLINDUNGAN TERHADAP ANAK DIDIK SEBAGAI KORBAN KEKERASAN FISIK DI SEKOLAH - Simatupang, Nursariani (MEDIA HUKUM, 2014)
The students are obliged to protect from the violence, including when the students are in the school.The conditions right now where the teachers consider the strict method with violence is still effective to control the students who transgress the rules at school, or make some mistakes. Whereas the ways of violence could cause the children having a psycology trauma and make them to imitate to do the same actions. The punishment that has been given to the students who commit some mistakes should be given correctly, fairly and wisely and based on the effection, but not being with violence or the punishment with hates. The punishments for the students should be able to be a motivation for them to be better. Because of that, as a teacher actually they understand the meaning of punishments that will be given to their students.